Profiling isokinetic strength by leg preference and position in rugby union athletes - Brown, S. R.; Brughelli, M.; Bridgeman, L. A. (International Journal of Sports Physiology and Performance, 2016)
Context: Muscle imbalances aid in the identification of athletes at risk for lower-extremity injury. Little is known regarding the influence that leg preference or playing position may have on lower-extremity muscle strength and asymmetry.